Exact Stiffness Matrices for Piles in Nonhomogeneous Elastic Foundation - Essa, Mohamad Jawad K. (Basrah Journal for Engineering Sciences, 2006)
This paper presents an exact solution for the load settlement relationship of axially loaded piles embedded in nonhomogeneous elastic foundation. The governing differential equation is reduced to modified Bessel equation of order v. The solution is represented by Bessel's functions of the first kind of order v. The stiffness coefficients are then derived from the exact solution. Numerical comparison with approximate solutions of special cases verify the accuracy and efficiency of the adopted method.